2022
DOI: 10.3389/fnut.2022.813899
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum HFY05 Attenuates Carrageenan-Induced Thrombosis in Mice by Regulating NF-κB Pathway-Associated Inflammatory Responses

Abstract: In this study, a carrageenan-induced thrombus model was established in mice to observe the ability of Lactobacillus plantarum KFY05 (LP-KFY05) to inhibit thrombosis through an NF-κB-associated pathway. Biochemical analysis, microscopical observations, quantitative polymerase chain reactions (qPCR) and western blot analysis were used to examine relevant serum and tissue indexes, and the composition of intestinal microorganisms was determined by examining the abundance of microorganisms in feces. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…Carrageenan is a sulphate-containing polysaccharide substance extracted from seaweed, which is a potent inflammatory substance. 54 After intraperitoneal injection into mice, it induces intravascular inflammation and the release of large amounts of inflammatory mediators, which disrupts the dynamic balance between coagulation and fibrinolysis, and ultimately induces thrombus formation. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Carrageenan is a sulphate-containing polysaccharide substance extracted from seaweed, which is a potent inflammatory substance. 54 After intraperitoneal injection into mice, it induces intravascular inflammation and the release of large amounts of inflammatory mediators, which disrupts the dynamic balance between coagulation and fibrinolysis, and ultimately induces thrombus formation. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…NF-κB is phosphorylated and translocated into the nucleus to trigger acute inflammation in the cardiomyocytes. It was shown that the role of NF-κB in myocardial inflammation is enacted by promoting the expression of inflammatory factors [ 50 , 51 ]. In our study, the effect of HF on the suppression of the NF-κB signaling pathway was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse blood was collected 2 h after injection with carrageenan. First, 250 μL of plasma supernatant from each group was used to prepare platelet-poor plasma [ 1 ]. Then, APTT, PT, TT and FIB were determined using the corresponding assay kits strictly according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Cardiovascular diseases have become a critical threat to human health due to the improvement of living standards and changes of dietary patterns in recent years [ 1 ]. Thrombosis, the formation of thrombus in a blood vessel, is a main cause of cardiovascular diseases, which influence its occurrence and progression [ 2 ].…”
Section: Introductionmentioning
confidence: 99%